Influence of polymerisation on the reversibility of low-energy proton exchange reactions by Para-Aminothiolphenol. Issue 1 (December 2017) - Balakrishnan, Divya; Lamblin, Guillaume; Thomann, Jean; Guillot, Jerome; Duday, David; Berg, Albert; Olthuis, Wouter; Pascual-García, César
Abstract The reversibility of redox processes is an important function for sensing and molecular electronic devices such as pH reporters or molecular switches. Here we report the electrochemical behaviour and redox reversibility of para-aminothiolphenol (PATP) after different polymerisation methods. We used electrochemical and photo-polymerisation in neutral buffers and plasma polymerisation in air to induce reversible redox states. The chemical stoichiometry and surface coverage of PATP in the polymerized layers were characterized by X-ray photoelectron spectroscopy (XPS), while cyclic voltammetry (CV) was used to measure the charge transfer, double layer capacitance and electrochemical rate of the layers during successive potential cycles. Our results show that the surface coverage of the redox active species is higher on electro-polymerised samples, however, after consecutive cycles all the methods converge to the same charge transfer, while the plasma polymerised samples achieve higher efficiency per molecule and UV polymerised samples have a higher electron transfer rate.